Influence of Price and Brand Recognition on Online Fashion Product Purchase Decisions with Trust as a Mediating Variable on the Shopee Platform in Padang City - Haris Ahmadi; Yunia Wardi (SAFE-Network, 2026)
This study aims to analyze the effect of price and brand recognition on online fashion product purchase decisions on the Shopee platform in Padang City with trust as a mediating variable. This research uses a quantitative approach with a causal research design. The sampling technique used purposive sampling with a total sample of 200 respondents who are consumers in Padang City who have purchased fashion products through the Shopee platform. Research data were collected through the distribution of online questionnaires using Google Forms and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results show that Price does not influence the decision to purchase fashion products online on the Shopee platform in Padang City, brand recognition has a positive and significant effect on purchase decisions, price has a positive and significant effect on trust, brand recognition has a positive and significant effect on trust, trust has a positive and significant effect on purchase decisions, trust is able to mediate the effect of price on purchase decisions, and trust is able to mediate the effect of brand recognition on purchase decisions. These findings indicate that consumer trust is an important factor in encouraging purchase decisions in e-commerce transactions. Strong brand recognition and reasonable price perceptions can increase consumer trust and ultimately encourage purchase decisions.